Elaborasi Ayat-Ayat Sains dalam Al-Quran: Langkah Menuju Integrasi Agama dan Sains dalam Pendidikan - Septiana Purwaningrum (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2015)
Integration of scienceandreligionis an alternativemodel ofeducationwhich is consideredessential toachieve thegoalof nationaleducationas mandatedby theEducation LawNo.202003.The developmentmodel ofintegration of scienceandreligioncan be donein stagesthroughthree things, namely: mapping thescientific and Islamicconcepts, combiningscientific and Islamicconcepts, and makeal-Quran andHadithasthe guardianofeveryworkof science. It is difficultindeed, butnot animpossiblethingtodo.The first step thatneeds tobeteacherstoimplementthisintegrativeeducational modelistheway ofdoingsciencegroupingversesin the Quran. After that, a teachermustdo theelaborationof materialsciencewith averse from the Qur'anand hadith, by making theKoranas aguardateveryworkof science.The purposeofthiselaborationis to providea comprehensive understanding ofthestudentsto adiscussion, whichin turn canbringgoodgradesfor studentsinliving her life.